EDUCATORS STRATEGIES IN IMPLEMENTING MORAL EDUCATIONIN THE DIGITAL ERA - Syafiq Asyaraf; faizan faruq; Fiqra Nazib (Advances In Education Journal, 2024)
The purpose of this study is to identify educators' strategies in instilling moral education in the digital era. This article is based on a literature review method, allowing the author to gather various relevant information. Educators' strategies in embedding moral education in the digital era aim to facilitate teaching processes using technology. Digitalization impacts life order, mindset changes, and lifestyle shifts. A common concern is internet misuse, potentially causing moral degradation among students. Moral education is crucial from an early age, as it is the optimal time to provide positive stimuli to children. Early moral education significantly influences a child's moral development and is a primary priority for both parents at home and educators at school. Effective moral education requires appropriate methods to help children self-regulate in digital media usage, leveraging technological advancements for beneficial purposes. Applicable methods in the digital era include exemplification, habituation, advice, attention, punishment, and supervision.